KESESUAIAN HASIL PEMERIKSAAN FINE NEEDLE ASPIRATION BIOPSY (FNAB) DENGAN PEMERIKSAAN HISTOPATOLOGY DALAM MENENTUKAN TUMOR PAYUDARA: ACCORDANCE OF FINE NEEDLE ASPIRATION BIOPSY (FNAB) EXAMINATION RESULTS WITH HISTOPATHOLOGY EXAMINATION IN DETERMINING BREAST TUMORS - Rate, Inggit Wigati; Santoso, Setyo Dwi; Anggrenani, Tri Endah (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2024)
Breast tumors are a collection of cells in the breast tissue that divide rapidly so that they grow and become numerous. Breast tumors are divided into 2, namely benign tumors and malignant tumors (cancer). One way to establish a diagnosis of breast tumors is by examining Fine Needle Aspiration Biopsy (FNAB) and histopathology which are the gold standard of diagnosis. The purpose of this study was to determine the suitability of FNAB examination with Histopathology in determining benign or malignant breast tumors, as well as to determine the sensitivity, specificity, positive predictive value, negative predictive value and accuracy. This study used a descriptive research method with a sample size of 96 samples in 2022. The results of the study showed that there was a match between the results of the FNAB examination and the histopathology examination in determining benign or malignant breast tumors. In this study, FNAB had a sensitivity value of 83.78%, a specificity of 95.45%, a positive predictive value of 98.41%, a negative predictive value of 63.64% and an accuracy of 86.46%. It was concluded that the Fine Needle Aspiration Biopsy (FNAB) examination was consistent with the Histopathology examination in determining tumors